Genome‐Wide Population Structure in a Marine Keystone Species, the European Flat Oyster ( Ostrea edulis ) - Homère J. Alves Monteiro; Dorte Bekkevold; George Pacheco; Stein Mortensen; Runyang Nicolas Lou; Nina O. Therkildsen; Arnaud Tanguy; Chloé Robert; Pierre De Wit; Dorte Meldrup; Ane T. Laugen; Philine S. E. zu Ermgassen; et al. (Molecular Ecology, 2025)
Ostrea edulis, the European flat oyster, was once a widespread economically and ecologically important marine species, but has suffered dramatic declines over the past two centuries. Consequently, there has been a surge in European restoration efforts, many of which focus on restocking as a conservation measure. In this study, we used whole‐genome sequencing (WGS) data to investigate the population structure, demographic history, and patterns of local adaptation of O. edulis across its natural distribution with increased sampling densities at Scandinavian localities. Results revealed seven distinct genetic clusters, including previously undescribed complex population structure in Norway, and evidence for introgression between genetic clusters in Scandinavia. We detected large structural variants (SVs) on three pseudo‐chromosomes. These megabase long regions were characterised by strong linkage disequilibrium and clear geographical differentiation, suggestive of chromosomal inversions potentially associated with local adaptation. The results indicated that genomic traces of past translocations of non‐native O. edulis were still present in some individuals, but overall, we found limited evidence of major impacts of translocations on the scale of contemporary population structure. Our findings highlight the importance of considering population structure and signatures of selection in the design of effective conservation strategies to preserve and restore wild native European flat oyster populations, and we provide direct knowledge safeguarding sustainable mitigation actions in this important species.

The gut microbiome differs between hygiene-performing and non-hygiene-performing worker honey bees - Y. H. Tola; K. Wagoner; M. K. Strand; O. Rueppell; D. R. Tarpy (Insectes Sociaux, 2025)
Gut microbiomes play a significant role in the health, development, and behavior of numerous species, including honey bees ( Apis mellifera ). Worker honey bees exhibit varying degrees of hygienic behavior, which involves the removal of unhealthy brood to mitigate disease within their colony. However, the potential relationship between hygienic behavior and the honey bee gut microbiome has not been previously investigated. In this study, we compared gut microbiota in honey bees engaged in hygienic behavior (hygiene performers) versus those not exhibiting this behavior (non-hygiene performers) using 16S rRNA gene amplicon sequencing. Proteobacteria, Firmicutes, and Actinobacteria were identified as the predominant phyla. Notably, three bacterial species ( Apilactobacillus kunkeei , Bartonella apis, and Frischella perrara ) were found to be more abundant in hygiene performer bees compared to non-hygiene performer bees. Additionally, hygiene performer bees showed a higher diversity of amplicon sequence variants, with Apibacter mensalis being exclusively present in hygiene performer bees and absent in non-hygiene performer bees. These findings reveal an association between gut microbiota composition and hygienic behavior in honey bees, which may provide a foundation for future research exploring probiotic development and other strategies to enhance honey bee health.

Spatial predictive modeling of soil organic carbon stocks in Norwegian forests - Andreas Hagenbo; Lise Dalsgaard; Marius Hauglin; Stephanie Eisner; Line Tau Strand; O. Janne Kjønaas (Science of The Total Environment, 2025)

P25-12 Effects of personalized chemical mixture on endocrine disruption based on estrogen nuclear receptors - L. Reis; D. Strand; B. Lundgren; J. Martin; O. Karlsson (Toxicology Letters, 2024)

P25-13 Effects of personalized mixtures of POPs on steroidogenesis and viability in H295R cells - D. Strand; B. Lundgren; J.W. Martin; O. Karlsson (Toxicology Letters, 2024)

Microcystin profiles in European noble crayfish Astacus astacus and water in Lake Steinsfjorden, Norway - Christopher O. Miles; David A. Strand; Johannes C. Rusch; Andreas Ballot; Sigrid Haande; Kjersti L.E. Løvberg; Trude Vrålstad; Ingunn A. Samdal (Environmental Research, 2024)

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Global stakeholder vision for ecosystem‐based marine aquaculture expansion from coastal to offshore areas - Ibon Galparsoro; Arantza Murillas; Kemal Pinarbasi; Ana M.M. Sequeira; Vanessa Stelzenmüller; Ángel Borja; Anne Marie O´Hagan; Adele Boyd; Suzanne Bricker; Joxe Mikel Garmendia; Antje Gimpel; Aline Gangnery; et al. (Reviews in Aquaculture, 2020)
Marine aquaculture is the most promising industry for ensuring future provision of seafood. Yet, the worldwide growth and expansion of this industry have been slower than expected, calling for the identification of environmentally suitable sites while accounting for all factors that could constrain or benefit its establishment. Here, we determine the main obstacles and risks hindering the growth and expansion of marine aquaculture, as well as the needs and recommendations to overcome such constraints. Our analysis is based on results obtained from a consultation process held in 16 study sites located around the world with the participation of 614 stakeholders representing the research community, aquaculture industry, government, conservation groups, and education and fishermen associations. A high level of commonality exists in the main issues hindering aquaculture growth and expansion in coastal, off‐the‐coast and offshore aquaculture with most being attributed to interactions with other maritime activities, including conflicts with other users and administrative procedures, including licensing. Critical needs for improved management and expansion of the aquaculture industry are related to planning and management of developments and technological advances, with economic and market needs featuring to a lesser extent. Key procedures recommended to assist further aquaculture growth are the standardisation and simplification of regulatory frameworks, improvement of governance, and the adoption of participatory processes to facilitate meaningful and productive stakeholder engagement. We strongly recommend stakeholder participation to enhance insights on the full environmental and human dimensions of marine management and for implementation of ecosystem‐based marine spatial planning.

Light-Weight Portable Electroantennography Device as a Future Field-Based Tool for Applied Chemical Ecology - Stephen M. Pawson; Jessica L. Kerr; Brooke C. O’Connor; Philippe Lucas; Dominique Martinez; Jeremy D. Allison; Tara M. Strand (Journal of Chemical Ecology, 2020)

Uncertainty Quantification and Sensitivity Analysis for Computational FFR Estimation in Stable Coronary Artery Disease - Fredrik E. Fossan; Jacob Sturdy; Lucas O. Müller; Andreas Strand; Anders T. Bråten; Arve Jørgensen; Rune Wiseth; Leif R. Hellevik (Cardiovascular Engineering and Technology, 2018)

Attraction and repulsion of mobile wild organisms to finfish and shellfish aquaculture: a review - Myriam D. Callier; Carrie J. Byron; David A. Bengtson; Peter J. Cranford; Stephen F. Cross; Ulfert Focken; Henrice M. Jansen; Pauline Kamermans; Anders Kiessling; Thomas Landry; Francis O'Beirn; Erik Petersson; et al. (Reviews in Aquaculture, 2018)
Knowledge of aquaculture–environment interactions is essential for the development of a sustainable aquaculture industry and efficient marine spatial planning. The effects of fish and shellfish farming on sessile wild populations, particularly infauna, have been studied intensively. Mobile fauna, including crustaceans, fish, birds and marine mammals, also interact with aquaculture operations, but the interactions are more complex and these animals may be attracted to (attraction) or show an aversion to (repulsion) farm operations with various degrees of effects. This review outlines the main mechanisms and effects of attraction and repulsion of wild animals to/from marine finfish cage and bivalve aquaculture, with a focus on effects on fisheries‐related species. Effects considered in this review include those related to the provision of physical structure (farm infrastructure acting as fish aggregating devices ( FAD s) or artificial reefs ( AR s), the provision of food (e.g. farmed animals, waste feed and faeces, fouling organisms associated with farm structures) and some farm activities (e.g. boating, cleaning). The reviews show that the distribution of mobile organisms associated with farming structures varies over various spatial (vertical and horizontal) and temporal scales (season, feeding time, day/night period). Attraction/repulsion mechanisms have a variety of direct and indirect effects on wild organisms at the level of individuals and populations and may have implication for the management of fisheries species and the ecosystem in the context of marine spatial planning. This review revealed considerable uncertainties regarding the long‐term and ecosystem‐wide consequences of these interactions. The use of modelling may help better understand consequences, but long‐term studies are necessary to better elucidate effects.

A new ensemble of GCM simulations to assess avoided impacts in a climate mitigation scenario - Benjamin M. Sanderson; Keith W. Oleson; Warren G. Strand; Flavio Lehner; Brian C. O’Neill (Climatic Change, 2018)

The Northeast Greenland Shelf as a Potential Habitat for the Northeast Arctic Cod - Kjersti O. Strand; Svein Sundby; Jon Albretsen; Frode B. Vikebø (Frontiers in Marine Science, 2017)

Lessons from the First Generation of Marine Ecological Forecast Products - Mark R. Payne; Alistair J. Hobday; Brian R. MacKenzie; Desiree Tommasi; Danielle P. Dempsey; Sascha M. M. Fässler; Alan C. Haynie; Rubao Ji; Gang Liu; Patrick D. Lynch; Daniela Matei; Anna K. Miesner; et al. (Frontiers in Marine Science, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Irisin and FNDC5: effects of 12-week strength training, and relations to muscle phenotype and body mass composition in untrained women - S. Ellefsen; O. Vikmoen; G. Slettaløkken; J. E. Whist; H. Nygaard; I. Hollan; I. Rauk; G. Vegge; T. A. Strand; T. Raastad; B. R. Rønnestad (European Journal of Applied Physiology, 2014)

Impact of early salmon louse, L epeophtheirus salmonis , infestation and differences in survival and marine growth of sea‐ranched A tlantic salmon, S almo salar L., smolts 1997–2009 - O T Skilbrei; B Finstad; K Urdal; G Bakke; F Kroglund; R Strand (Journal of Fish Diseases, 2013)
The impact of salmon lice on the survival of migrating A tlantic salmon smolts was studied by comparing the adult returns of sea‐ranched smolts treated for sea lice using emamectin benzoate or substance EX with untreated control groups in the R iver D ale in western N orway. A total of 143 500 smolts were released in 35 release groups in freshwater from 1997 to 2009 and in the fjord system from 2007 to 2009. The adult recaptures declined gradually with release year and reached minimum levels in 2007. This development corresponded with poor marine growth and increased age at maturity of ranched salmon and in three monitored salmon populations and indicated unfavourable conditions in the N orwegian S ea. The recapture rate of treated smolts was significantly higher than the controls in three of the releases performed: the only release in 1997, one of three in 2002 and the only group released in sea water in 2007. The effect of treating the smolts against salmon lice was smaller than the variability in return rates between release groups, and much smaller that variability between release years, but its overall contribution was still significant ( P 0.05) and equivalent to an odds ratio of the probability of being recaptured of 1.17 in favour of the treated smolts. Control fish also tended to be smaller as grilse ( P = 0.057), possibly due to a sublethal effect of salmon lice.

Does increased abundance of sea lice influence survival of wild Atlantic salmon post‐smolt? - N. A. Hvidsten; B. Finstad; F. Kroglund; B. O. Johnsen; R. Strand; J. V. Arnekleiv; P. A. Bjørn (Journal of Fish Biology, 2007)
A synthesis of results from two projects was assessed to analyse possible influence of sea lice Lepeophtheirus salmonis on marine Atlantic salmon Salmo salar survival. During the years 1992–2004, trawling for wild migrating post‐smolts was performed in Trondheimsfjord, a fjord in which no Atlantic salmon aquaculture activity is permitted. Prevalence and intensity of sea lice infections on migrating wild post‐smolts differed between years. A correlation analysis between 1 sea‐winter (SW) Atlantic salmon catch statistics from the River Orkla (a Trondheimsfjord river) and sea lice infections on the migrating smolts in the Trondheimsfjord was not significant. Up to 2% reduction in adult returns due to sea‐lice infection was expected. In addition, experimental releases from 1996 to 1998 with individually tagged groups of hatchery‐reared Atlantic salmon smolts given protection against sea‐lice infection was performed. Higher recaptures of adult Atlantic salmon from 1998 treated smolts compared to the control group may correspond to high abundance of sea lice found on the wild smolt, and may indicate influence on post‐smolt mortality. These studies indicate that post‐smolt mortality in Trondheimsfjord is marginally influenced by sea lice infection; however, the methods for assessing wild smolt mortality might be insufficient. Higher infections of sea lice farther out in the fjord may indicate more loss in Atlantic salmon returns in some years.

Population structure in a critically endangered arctic fox population: does genetics matter? - L. DALÉN; K. KVALØY; J. D. C. LINNELL; B. ELMHAGEN; O. STRAND; M. TANNERFELDT; H. HENTTONEN; E. FUGLEI; A. LANDA; A. ANGERBJÖRN (Molecular Ecology, 2006)
The arctic fox ( Alopex lagopus ) in Scandinavia is classified as critically endangered after having gone through a severe decline in population size in the beginning of the 20th century, from which it has failed to recover despite more than 65 years of protection. Arctic foxes have a high dispersal rate and often disperse over long distances, suggesting that there was probably little population differentiation within Scandinavia prior to the bottleneck. It is, however, possible that the recent decline in population size has led to a decrease in dispersal and an increase in population fragmentation. To examine this, we used 10 microsatellite loci to analyse genetic variation in 150 arctic foxes from Scandinavia and Russia. The results showed that the arctic fox in Scandinavia presently is subdivided into four populations, and that the Kola Peninsula and northwest Russia together form a large fifth population. Current dispersal between the populations seemed to be very low, but genetic variation within them was relatively high. This and the relative F ST values among the populations are consistent with a model of recent fragmentation within Scandinavia. Since the amount of genetic variation is high within the populations, but the populations are small and isolated, demographic stochasticity seems to pose a higher threat to the populations’ persistence than inbreeding depression and low genetic variation.

Lysimeter Study on the Effects of Different Rain Qualities on Element Fluxes from Shallow Mountain Soils in Southern Norway - L. T. Strand; G. Abrahamsen; A. O. Stuanes (Water, Air, & Soil Pollution, 2005)

Testicular atrophy and loss of nerve growth factor-immunoreactive germ cell line in rats exposed to n-hexane and a protective effect of simultaneous exposure to toluene or xylene - Per Nyln; Ted Ebendal; Maria Eriksdotter-Nilsson; Tiiu Hansson; Andreas Henschen; Ann-Christin Johnson; Tony Kronevi; Ulrik Kvist; Nils O. Sjstrand; Gunnar Hglund; Lars Olson (Archives of Toxicology, 1989)